Heart Failure Impairs Bone Marrow Hematopoietic Stem Cell Function and Responses to Injury - Tina B. Marvasti; Faisal J. Alibhai; Grace J. Yang; Shu‐Hong Li; Jun Wu; Terrence Yau; Ren‐Ke Li (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Heart failure (HF) is a clinical syndrome associated with a progressive decline in myocardial function and low‐grade systemic inflammation. Chronic inflammation can have lasting effects on the bone marrow (BM) stem cell pool by impacting cell renewal and lineage differentiation. However, how HF affects BM stem/progenitor cells remains largely unexplored. Methods and Results EGFP+ (Enchanced green fluorescent protein) mice were subjected to coronary artery ligation, and BM was collected 8 weeks after myocardial infarction. Transplantation of EGFP+ BM into wild‐type mice revealed reduced reconstitution potential of BM from mice subjected to myocardial infarction versus BM from sham mice. To study the effects HF has on human BM function, 71 patients, HF (n=20) and controls (n=51), who were scheduled for elective cardiac surgery were consented and enrolled in this study. Patients with HF exhibited more circulating blood myeloid cells, and analysis of patient BM revealed significant differences in cell composition and colony formation potential. Human CD34+ cell reconstitution potential was also assessed using the NOD‐SCID‐IL2rγnull mouse xenotransplant model. NOD‐SCID‐IL2rγnull mice reconstituted with BM from patients with HF had significantly fewer engrafted human CD34+ cells as well as reduced lymphoid cell production. Analysis of tissue repair responses using permanent left anteriordescending coronary artery ligation demonstrated reduced survival of HF‐BM reconstituted mice as well as significant differences in human (donor) and mouse (host) cellular responses after MI. Conclusions HF alters the BM composition, adversely affects cell reconstitution potential, and alters cellular responses to injury. Further studies are needed to determine whether restoring BM function can impact disease progression or improve cellular responses to injury.